Pengaruh Model Pembelajaran Inkuiri Berbantuan Media Video Terhadap Hasil Belajar Siswa dalam Pembelajaran IPA Kelas V SD Inpres 3 Tondo - Riska Pramudia Rinanda (JURNAL DIKDAS, 2026)
The purpose of this research is to determine the effect of inquiry learning model assisted by video media on science learning outcomes classes of fifth grade students of SD Inpres 3 Tondo. The research method is quasi experimental design and research design nonequivalent control group design. The population of the study was all VA and VB class students which consited 46 students.This research used purposive sampling saturated, namely taking samples with certain considerations of 46 students. Data collection techniques used test and non-test techniques. Based on hypothesis testing using the paired sample T test at a real level of 5% (0,05), a significant value of 0,000 was obtained. Because the significant value of the T- test is <0.05 (0.000 < 0.05) Ha is a accepted and Ho is rejected. Thus,it can be concluded that there is a influences of the inquiri learning model assisted by video media on science learning outcomes and differences in science learning outcomes between experimental and control classes of fifth grade student of SD Inpres 3 Tondo.